Redox Imbalance in Lung Cancer of Patients with Underlying Chronic Respiratory Conditions - Mercè Mateu-Jiménez; Albert Sánchez-Font; Alberto Rodríguez-Fuster; Rafael Aguiló; Lara Pijuan; Clara Fermoselle; Joaquim Gea; Víctor Curull; Esther Barreiro (Molecular Medicine, 2016)
Abstract Chronic respiratory diseases such as obstructive pulmonary disease (COPD) and oxidative stress may underlie lung cancer (LC). We hypothesized that the profile of oxidative and antioxidant events may differ in lung tumors and blood compartments of patients with non-small cell LC (NSCLC) with and without COPD. Redox markers (immunoblotting, ELISA, chemiluminescence, 2D electrophoresis and proteomics) were analyzed in blood samples of 17 control subjects and 80 LC patients (59 LC-COPD and 21 LC) and lung specimens (tumor and nontumor) from those undergoing thoracotomy (35 patients: 23 LC-COPD and 12 LC). As smoking history was more prevalent in LC-COPD patients, these were further analyzed post hoc as heavy and moderate smokers (cutoff, 60 pack-years). Malondialdehyde (MDA)-protein adducts and SOD1 levels were higher in tumor and nontumor samples of LC-COPD than in LC. In tumors compared with nontumors, SOD2 protein content was greater, whereas catalase levels were decreased in both LC and LC-COPD patients. Blood superoxide anion levels, protein carbonylation and nitration were greater in LC and LC-COPD patients than in the controls, and in the latter patients compared with the former. Systemic superoxide anion, protein carbonyls and nitrotyrosine above specific cutoff values best identified underlying COPD among all patients. Smoking did not influence the study results. A differential expression profile of oxidative stress markers exists in blood and, to a lesser extent, in the tumors of LC-COPD patients. These findings suggest that systemic oxidative stress and lung antioxidants (potential biomarkers) may predispose patients with chronic respiratory diseases to a higher risk for LC.